Orbito-Cranial Injury Caused by Penetrating Wooden Piece - Gautam, P; Shah, DN (Journal of Institute of Medicine Nepal, 2013)
We present the case of a 35-year-old man with history of fall 2 days back and an upperlid laceration with foreign body seen in the wound with a new onset of seizure disorder that was found to harbor anintra-parenchymal foreign body related to orbital trauma. Imaging revealed a pneumo-cephalus in the extra-axial space over right frontal lobe anterior pole with focal laceration in basal area of frontal lobe with an obliquely oriented fat/ air attenuating foreign body lodged in the basal area of frontal lobe extending from roof of orbit medially with foreign body indenting the right globe inferiorly.